2021
DOI: 10.1590/1516-3180.2020.0116.r1.18112020
|View full text |Cite
|
Sign up to set email alerts
|

Popular knowledge of stroke in São Paulo: a cross-sectional study within the World Stroke Campaign

Abstract: BACKGROUND: Stroke is the second leading cause of death in Brazil and the main cause of disability. Inability to identify alarm signals causes delays in seeking emergency services, thereby leading to a worse prognosis. OBJECTIVES: To assess the population's knowledge of how to recognize and prevent stroke. DESIGN AND SETTING: Prospective cross-sectional study on data derived from a questionnaire that was administered during the 2016 World Stroke Campaign, launched in the city of São Paulo, Brazil. METHODS: Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Several studies [9][10][11][12] have shown the effectiveness of stroke awareness campaigns regarding the detection of stroke signs and the intention to call emergency medical services. A Brazilian prospective cross-sectional study 13 conducted in the context of the World Stroke Campaign in 2016 showed that 47.9% of the participants did not know how to define stroke, only 18.1% listed three or more stroke symptoms, and 29.03% listed three or more risk factors. This study 13 also showed that people with low levels of schooling (incomplete Elementary School) were 6.1 times more likely to have poor knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [9][10][11][12] have shown the effectiveness of stroke awareness campaigns regarding the detection of stroke signs and the intention to call emergency medical services. A Brazilian prospective cross-sectional study 13 conducted in the context of the World Stroke Campaign in 2016 showed that 47.9% of the participants did not know how to define stroke, only 18.1% listed three or more stroke symptoms, and 29.03% listed three or more risk factors. This study 13 also showed that people with low levels of schooling (incomplete Elementary School) were 6.1 times more likely to have poor knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Some Brazilian studies recognized “derrame” [ 8 , 10 , 12 , 13 , 15 ] as a common alternative name for stroke. Indeed it is widely used in lay media [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about other symptoms related to stroke was poor, however similar to another study that applied a strategy similar [ 10 ] to ours (the main cited symptoms were headache and cognition problems, both by 8.1% of their sample). In general, the most common signs and symptoms cited in Brazilian studies applying an open-ended approach [ 12 , 13 , 17 , 18 ] are motor (facial drop and/or hemiplegia), language impairment, headache and paresthesia, with a frequency around 30 − 20%. This frequency was similar in developed countries [ 7 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this assumption, it is therefore imperative that the population should possess knowledge concerning stroke; be able to recognize the risk factors, signs and symptoms; and be aware of preventive measures for this condition, as well as the correct conduct when faced with a stroke. 5 With this in mind, it can be understood that this knowledge is important for the young population, since many of these individuals, after leaving high school, will take up jobs in places with large gatherings of people, such as shopping malls, airports or parks. They should therefore be able to recognize the signs and symptoms of stroke, so that the emergency services can be called.…”
Section: Introductionmentioning
confidence: 99%